On a Corporate Bond Pricing Model with Credit Rating Migration Risksand Stochastic Interest Rate - Jin Liang; Hong-Ming Yin; Xinfu Chen; Yuan Wu (Quantitative Finance and Economics, 2017)
In this paper we study a corporate bond-pricing model with credit rating migration and astochastic interest rate. The volatility of bond price in the model strongly depends on potential creditrating migration and stochastic change of the interest rate. This new model improves the previousexisting models in which the interest rate is considered to be a constant. The existence, uniquenessand regularity of the solution for the model are established. Moreover, some properties includingthe smoothness of the free boundary are obtained. Furthermore, some numerical computations arepresented to illustrate the theoretical results.